The Proficiency of Undergraduates in Utilizing Social Media for Learning in Nigeria - Onojah, Amos Ochayi; Obielodan, Omotayo Olabo; Onojah, Adenike Aderogba; Ajala, Akinkunmi Solomon; Sotuminu, Roseline Enuwa; Sulaimon, Keji Sakiru (Universitas Negeri Semarang, 2020)
Students use social media for social activities more than learning but studies on the proficiency for learning has been less researched. This study therefore assessed the undergraduate students’ proficiency’ level of utilizing social media for learning in Nigeria. The study employed the quantitative research method. Four hundred and fifty (450) respondents were randomly sampled across universities in Nigeria on which a structured questionnaire was administered on the students. The research questions were answered using mean, while t-test statistic was used to test the two hypotheses. Results of the research revealed that the proficiency level of undergraduates on the utilization of social media for learning was high and there was no significant difference between male and female undergraduates' utilization and undergraduates' proficiency towards the utilization of social media for learning. The study concluded that undergraduate students have good proficiency level on the utilization of social media for learning. Abstrak Siswa-siswa sekarang banyak menggunakan media sosial sekadar untuk aktivitas sosial ketimbang belajar, hanya saja kajian untuk hal ini relatif minim. Penelitian ini mengkaji tingkat kemahiran mahasiswa S1 dalam penggunaan media sosial untuk pembelajaran di Nigeria. Penelitian ini menggunakan metode kuantitatif dan melibatkan 450 responden yang dipilih secara acak dari seluruh universitas di Nigeria menggunakan kuesioner terstruktur untuk para siswa. Pertanyaan penelitian ini dijawab menggunakan rata-rata dan analisis statistik t-test digunakan untuk menguji hipotesisnya. Hasil penelitian ini menunjukkan bahwa level kemahiran/penguasaan mahasiswa dalam menggunakan media sosial untuk pembelajaran tinggi dan tidak ada perbedaan antara mahasiswa laki-laki dan perempuan. Penelitian ini menyimpulkan bahwa mahasiswa S1 memiliki tingkat kemahiran yang bagus dalam menggunakan media sosial untuk pembelajaran.